EMI as a estrategic tool in the internationalisation at home process in higher education - Emmanuelle Pereira da Costa e Cardoso (2024)
Institutions of higher education have undergone major transformations globally due to the implementation of actions aimed at internationalisation. Knight (2016) points out that these institutions must understand that the internationalisation process is imminent and can encompass a series of actions, such as curricular internationalisation (or internationalisation at home). The pedagogical approach called English Medium Instruction (EMI) is an important and integral part of the internationalisation process, proposing that classes be taught in English. To this end, this research seeks to investigate how the internationalisation process has developed in the context of the Federal University of Minas Gerais (UFMG, Universidade Federal de Minas Gerais), particularly regarding the adoption of EMI in higher education. The main objective of this research is to develop collaborative work between content teachers and an English teacher to provide pedagogical support to those participating in university’s internationalisation project. Based on a mapping of the actions that the university has developed, we proposed collaborative work between the EMI content teachers and the specialist teacher. Thus, an analysis of the linguistic needs of the students in the disciplines investigated was carried out, specifically in the areas of psychology, dentistry, and business administration. From the results of this analysis, we created didactic activities to address the main difficulties the students presented. This linguistic support was based on specialised corpora, directed to the disciplines participating in this research, providing exposure to relevant and authentic data. It is expected that the results of this research will support future applications of EMI, contributing to the advancement of actions aimed at curricular internationalisation in the scope of higher education.